Sustainable aquaculture and community fish refuge management (khmer) - Sean, Vichet; Ou, Phichong; Sun, Vathanak (WorldFish, 2024)
The Sustainable Aquaculture and Community Fish Refuge (SAFR) project, which falls under the BMZ Special Initiative “Transformation of Agricultural and Food Systems,” aims to reduce poverty and hunger. Under the BMZ initiative, the Global Programme Sustainable Fisheries and Aquaculture was launched to improve the availability of fish products for food insecure people and increase employment and incomes. Thanks to contributions from the SAFR, the Cambodia Fisheries Administration was able to meet its goal of establishing 1200 community fish refuges (CFRs) to increase fish production, create jobs and generate income from environmentally friendly rice fields for food insecure people. To achieve this, WorldFish implemented the project CFR component (SAFR-CFR) to establish and improve the 21 CFRs in Kampong Thom. The project lasted from December 2020 to March 2024.